The Effect of Social Skills and Social Support on Student Resilience in Schools - Prio Utomo; Reza Pahlevi; Fiki Prayogi (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2022)
One aspect of the success of students being able to achieve self-welfare is resilience. The purpose of this study was to determine the effect of social skills and social support on student resilience. This research was conducted at SMP Negeri 10 Bengkulu. The research design used the one-short model correlation method. Data collection uses a scale of social skills, social support, and resilience. The instrument validity test uses the product-moment coefficient, and the reliability test uses the Cronbach alpha coefficient. Data analysis used prerequisite tests and hypotheses. The results showed that (1) the linear regression equation resulted in a constant value of 29.11; (b) the regression coefficient of 6.28; (2) the value of the correlation coefficient is 0.72; (3) the value of the coefficient of determination is 51.84%. The results of the analysis show that there is an influence between social skills and social support on student resilience at school (Ha is accepted and H0 is rejected). Suggestions and recommendations, for further researchers, are expected to reveal the role of social skills and social support as factors forming student resilience